Experimental Study of the Influence of Nanoparticles Additive to Diesel Fuel on the Emission Characteristics - Bunyan, Sadiq Talal; Hasan, Abed Al-Khadhim M. (Al-Khwarizmi Engineering Journal, 2021)
The present experimental work is conducted to examine the influence of adding Alumina (Al2O3) nanoparticles and Titanium oxide (TiO2) nanoparticles each alone to diesel fuel on the characteristic of the emissions. The size of both Alumina and Titanium oxide nanoparticles which have been added to diesel fuel to obtain nano-fuel is about 20 nm and 25 nm respectively. Three doses of (Al2O3) and (TiO2) were prepared (25, 50, and 100) ppm. The nanoparticles mixed with gas oil fuel by mechanical homogenous (manual electrical mixer) and ultrasonic processor. The study reveals that the adding of Aluminum oxide (Al2O3) and Titanium oxide (TiO2) to gas oil (Al2O3+DF) and (TiO2+DF) improves the emissions characteristic of the engine such as CO emissions are reduced by 34.28% and 20.5% for TiO2+DF and Al2O3+DF respectively at 25ppm, the emissions of CO2 increased by about 1.75% and 2.27% for TiO2+DF and Al2O3+DF respectively at 100ppm, the emissions of NOx decreased by about 37.7% and 12.2% for TiO2+DF and Al2O3+DF respectively at 25ppm and the emissions UHC decreased by about 16.9% and 13.5% for TiO2+DF and Al2O3+DF respectively at 25ppm.